Examining the Approach of Training the Mind based on the Perspective of Transcendental Wisdom with Emphasis on Strengthening Imagination in Children's Education - Akbar Panahi Dorcheh (Journal of Philosophical Investigations, 2022)
During the last two decades, the discussions related to "theory of children's mind" and the teachings related to the process of "mind training" have been widely promoted in the intellectual circles of the world. In such a way that half of the researches related to cognitive evolution in some countries have been related to "theory of mind". In our country, the project "teaching philosophy to children" was presented in order to strengthen and train the mind, which met with public approval. Although this project was severely criticized by some researchers, it played an effective role in strengthening the students' scientific foundation, acquiring problem solving skills and the training of the mind has played a role. This article, while stating the issue of "cognition" and "how to acquire knowledge", which is considered as an important and independent issue of conflicting opinions of thinkers in this field, examines the disagreement between the scholars of Masha and Sadr al-Mutalahin Shirazi in this field. Unlike other thinkers who consider the origin of "science" to be forms that dissolve in the soul and can be perceived in the form of "achievement", Mulla Sadra considers it to be the result of its invention and creation in the soul, which is "present" and with participation. "Imagination" is activated. Based on this, in the process of education, the training of mental powers alone is not enough for the growth and perfection of learners, and the strengthening of "imagination" should also be included in the agenda of the country's educational planners.